Apakah Analisis Rasio Keuangan Diperlukan? : Studi pada PT. Aneka Tambang 2016-2021 - Rusydina Sabila; Nofty Yoni; Vera Tessa Agustia Marshanda (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the financial performance of PT. Aneka Tambang Tbk in terms of financial ratios. This study uses 3 ratios namely Liquidity Ratio, Solvency Ratio, and Profitability Ratio. The research method used is descriptive quantitative. The data used is obtained from the financial statements of PT. Aneka Tambang Tbk 2016-2021. But in 2021 PT. Aneka Tambang Tbk succeeded in increasing its Liquidity Rasio. Solvency Rasio Analysis Also decreadased because teh campony was Not able to measure the value of the rasio of total debt to assets. Profitability rasio analysis also fluctuated but the company was still able to take advantage its assets.